2020
DOI: 10.5230/jgc.2020.20.e25
|View full text |Cite
|
Sign up to set email alerts
|

Application of Near-Infrared Fluorescence Imaging with Indocyanine Green in Totally Laparoscopic Distal Gastrectomy

Abstract: Purpose: Recently, totally laparoscopic gastrectomy has been gradually accepted by surgeons worldwide for gastric cancer treatment. Complete dissection of the lymph nodes and the establishment of the surgical margin are the most important considerations for curative gastric cancer surgery. Previous studies have demonstrated that indocyanine green (ICG)traced laparoscopic gastrectomy significantly improves the completeness of lymph node dissection. However, it remains difficult to identify the tumor location in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…ICG fluorescence laparoscopy has been applied in gastrointestinal surgery in recent years. Several studies have found that, in gastric cancer surgery, preoperative smaller doses of ICG injection in the submucosa around the tumor are conducive to clear imaging of tumor location intraoperatively, and indicate that ICG fluorescence laparoscope could be used to determine the accurate position of intraoperative tumors (18)(19)(20). These studies support the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…ICG fluorescence laparoscopy has been applied in gastrointestinal surgery in recent years. Several studies have found that, in gastric cancer surgery, preoperative smaller doses of ICG injection in the submucosa around the tumor are conducive to clear imaging of tumor location intraoperatively, and indicate that ICG fluorescence laparoscope could be used to determine the accurate position of intraoperative tumors (18)(19)(20). These studies support the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Patients in the ICG group experienced more lymph nodes excisions, which led to relative prolongation of operation time. In their experimental study, Liu et in radical gastrectomy of gastric cancer (19). This was confirmed in the studies of Pang et al, Zhong et al,.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The existing injection methods include the submucosal approach (SMA) and subserosal approach (SSA). The results of previous retrospective studies [ 2 , 3 ] and randomized controlled trial (RCT) [ 4 ] showed that submucosal injection of ICG around tumors 1 day before surgery could achieve good tracing of perigastric LNs, thus significantly increasing the overall number of retrieved LNs without increasing surgery-related complications in patients undergoing laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This facilitated tracing of the dissectible layer and enabled clear identification of the avascular plane as well as the distinction of blood vessels from surrounding lymphatic structures. According to these findings, ICG-enhanced guidance facilitates safe and complete infrapyloric lymph node dissection in terms of precision oncology with shorter operation time and less blood loss [ 16 , 17 ].…”
Section: Lymph Node Mapping With Icg-fi In Gastric Carcinomamentioning
confidence: 99%